Bibliometric analysis of theses of parasites in terrestrial fauna in the universities of Peru - García-Alcalde, Malory (2022)
The aim of this study was to know the scientific production through the bibliometric analysis of the pre- and postgraduate theses related to parasites of terrestrial fauna in the universities of Peru. The research was observational, retrospective, documentary and descriptive. Bibliographic searches were carried out in the virtual repositories of the universities of Peru between 2000 and 2021 and 403 theses related to parasitology of terrestrial fauna were reviewed in 32 universities of Peru. There was greater productivity at the undergraduate level (94.0%) and the university with the highest number of theses was the Universidad Nacional Mayor de San Marcos (UNMSM) (n=112). All the investigations were basic or pure, and the year of greatest support for this type of thesis was 2018. The samples used preferably came from the provinces (84.4%) and in the specialty of Veterinary Medicine (n=346), with the animal model being most used those belonging to the Mammalia class (n=370), especially in production animals (n=253). Regarding the follow-up of theses, only 20.4% were published as scientific articles, mostly in the Revista de Investigaciones Veterinarias del Perú (86.6%) in 2014. It is important that all undergraduate and postgraduate thesis work related to terrestrial fauna parasites culminate in a publication in a peerreviewed and indexed scientific journal.